PERANCANGAN SISTEM INFORMASI RETENSI REKAM MEDIS MENGGUNAKAN VISUAL BASIC.NET 2010 DI RSAU SALAMUN - Palapessy, Dwita Valensya; Siahaya, Welmina M.; Hidayati, Meira; Faza, Riky (JURSIMA, 2022)
The research conducted was motivated by retention activities in the hospital dr. M.Salamun where the activity is still used manually by way of officers sorting one by one medical records files that will be destroyed. The retention process that is done affects the performance of the officers because it requires energy and a long time. This research aims to create a retention information system so that it will greatly help medical records officers in processing medical records that will be destroyed and make retention reports. This research uses qualitative methods with descriptive approaches and for development methods used, namely waterfall methods with stages of system needs analysis, design, code, testing and maintenance. Observations, interviews and literature studies are conducted to collect data. For the software design stage starting from the flowmap creation stage, Data Flow Diagram level 0, Entity Relationship Diagram. Visual basic.Net is the programming language used while for databases using Microsoft access. The results of the research conducted showed that the retention information system created can make it easier for medical record personnel to sort out active and inactive medical records. This information system is also becoming more well integrated and effective and efficient.